El síndrome de alienación parental en los procesos judiciales por tenencia a razón de la Casación N° 2067-2010, en el distrito judicial de Huancavelica - 2015 - García Gonzalo, Dina (2023)
The research aimed to determine whether the judges of the Judicial District of Huancavelica, during the period 2015, took into account Parental Alienation Syndrome in custody judicial processes, in relation to cassation N° 2067-2010. It was a pure or basic research with a descriptive approach and a non-experimental descriptive design. The technique used was a survey, employing a questionnaire as the instrument